Berbudaya Melalui Media Digital - Meilani, Meilani (Humaniora, 2014)
Understanding and knowing the meaning of culture that shape the culture of a nation is the first step. Indonesia as a country that has various shades of different cultures from Sabang to Merauke, the diversity of cultural patterns is a matter of pride that should be preserved and passed on to generations of recipients so that its presence can be maintained. Do not let the culture of Indonesia is claimed by other countries simply because of ignorance and indifference to the Indonesian cultural heritage. Various means have been taken to promote the culture of the archipelago in conventional media such as magazines, books and even articles. Generations who have lived in abundance world of digital media technology is the next target of inheritance. So it would be nice if steps are taken to a great start to focus more on the spread of culture and passed it along the changing times and of course without losing the identity of the nation.